Peer effects on well-being and performance in elementary school - Isabel Skak Olufsen; Jesper Fries (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2025)
We study the effect of having high socioeconomic status (SES) peers on pupils' wellbeing, absence rate, and academic performance in elementary school. We compare pupils in the same school who started school in different years and, consequently, were exposed to different shares of high-SES peers. We use a unique combination of administrative, survey, and test data on pupils in Danish public schools. We find that a higher share of high-SES peers increases well-being and performance while lowering absence rates slightly. Our results imply that educational inequalities may increase due to the growing concentration of high-SES pupils in certain schools.
Keywords: I210; I240; I310; 330; peer effects; well-being; academic performance; primary school